2013
DOI: 10.1161/circoutcomes.111.000060
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Use of Prasugrel in Clinical Practice

Abstract: Background-Prasugrel is a recently approved thienopyridine for use in patients with acute coronary syndromes undergoing percutaneous coronary intervention. There are no data on contemporary use of prasugrel in routine clinical practice. Methods and Results-We assessed the patterns of prasugrel use among 55 821 patients who underwent percutaneous coronary intervention and were discharged alive from January 2010 to December 2011 at 44 hospitals participating in the Blue Cross Blue Shield of Michigan Cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…Whether this difference might reflect variations in practice patterns in the United States versus Europe (as suggested, for example, by considerable differences in the use of bare‐metal stent versus DES in the 2 studies) or relate to more contemporary treatment patterns in the present analysis (enrollment extended up to 2014 versus 2012 in TRANSLATE‐ACS) cannot be definitively addressed. Of note, real‐world observations indicate greater acceptance rates and a steady increase in the use of prasugrel over time 5, 28. Any thienopyridine cessation was associated with an increased risk of major adverse cardiac events in TRANSLATE ACS,27 which contrast with our present findings in a STEMI cohort as well as the findings of the PARIS registry6 in a broader PCI population.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Whether this difference might reflect variations in practice patterns in the United States versus Europe (as suggested, for example, by considerable differences in the use of bare‐metal stent versus DES in the 2 studies) or relate to more contemporary treatment patterns in the present analysis (enrollment extended up to 2014 versus 2012 in TRANSLATE‐ACS) cannot be definitively addressed. Of note, real‐world observations indicate greater acceptance rates and a steady increase in the use of prasugrel over time 5, 28. Any thienopyridine cessation was associated with an increased risk of major adverse cardiac events in TRANSLATE ACS,27 which contrast with our present findings in a STEMI cohort as well as the findings of the PARIS registry6 in a broader PCI population.…”
Section: Discussioncontrasting
confidence: 75%
“…Compared with clopidogrel, prasugrel provides rapid‐onset, more potent and consistent inhibition of platelet aggregation,3 and reduces the risk of cardiovascular mortality and stent thrombosis in patients with myocardial infarction (MI) 4. Prasugrel is recommended over clopidogrel following primary PCI1, 2 and is used increasingly in real‐world clinical practice 5…”
mentioning
confidence: 99%
“…In this sense, the article by Sandhu et al 12 (see page 293 of this issue) fills an important gap. This study is a timely and well-designed prospective registry of almost 56 000 consecutive patients with post-percutaneous coronary intervention.…”
Section: Article See Page 293mentioning
confidence: 99%
“…Furthermore, the authors found a steady increase in prasugrel use, with ≈22% of patients undergoing percutaneous coronary intervention on this therapy by study end. 12 It is disquieting that prasugrel contraindications have been ignored with a surprising frequency. This is not a sign of good clinical care and meticulous handling of potent pharmaceuticals.…”
Section: Article See Page 293mentioning
confidence: 99%
“…It was also shown that clopidogrel was effective enough in the carriers of wild-type (*1*1) CYP2C19, which represents a normal metabolism rate of this drug (Reese et al, 2012). In addition, only up to one-fourth of the prasugrel-treated patients are discharged from hospital for antiplatelet treatment at home (Sandhu et al, 2013;Bagai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%